2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580152
|View full text |Cite
|
Sign up to set email alerts
|

Models and methodology for optimal vehicle maneuvers applied to a hairpin turn

Abstract: Abstract-There is currently a strongly growing interest in obtaining optimal control solutions for vehicle maneuvers, both in order to understand optimal vehicle behavior and to devise improved safety systems, either by direct deployment of the solutions or by including mimicked driving techniques of professional drivers. However, it is nontrivial to find the right mix of models, formulations, and optimization tools to get useful results for the above purposes. Here, a platform is developed based on a stateof-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…A preliminary version of parts of the research presented here has been presented as conference contributions [27,28]. In this paper, several extensions are presented.…”
Section: Relation To Previous Work and Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…A preliminary version of parts of the research presented here has been presented as conference contributions [27,28]. In this paper, several extensions are presented.…”
Section: Relation To Previous Work and Outlinementioning
confidence: 99%
“…We use the force-slip tire characteristic surfaces as a basis for analysis, as introduced in [27] and hereafter referred to as Force-Slip (FS)-diagrams. This 3D Resulting Tire Force (WF) Table 3.…”
Section: Qualitative Behavior Of Tire Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Berntorp et al, 2013), which has to be solved on a receding horizon in real-time. As for the demonstrated scenario (and numerous other test runs with different curvatures and undergrounds) the curvature, the slip angle, and, none the less important, the vehicle velocity reference at the entrance of the curve are based on manually drifted manoeuvres.…”
Section: Discussionmentioning
confidence: 99%
“…The work presented here builds on the conclusions from [3]- [5], which showed that single-track models can replicate expert-driving behavior for high-level variables, such as yaw rate and velocity. It was also shown that the vehicle states are qualitatively similar for single-and double-track models when using an appropriate tire model, but the input torques and steer angles are significantly different.…”
Section: Introductionmentioning
confidence: 99%